Thermoplastic polyolefin alloy, preparation method thereof and application of thermoplastic polyolefin alloy in waterproof coiled material

By using a combination of polyethylene-1-butene block copolymer and polypropylene, a thermoplastic polyolefin alloy with high temperature resistance, thermal aging resistance, weather resistance, high strength, high elongation and flexibility is formed, and the existing waterproof coil materials have high hardness, poor resilience, unweather resistance and high cost are solved, and the effects of low density, high flexibility and excellent thermal aging resistance are achieved.

CN119842177APending Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311334020.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing TPV, TPO, POE and styrene butadiene elastomer modified asphalt used in waterproof coils have problems such as high modulus, high hardness, poor resilience, inequality and high cost.

Method used

Polyethylene-1-butene block copolymer is used as the main component of the elastic material, combined with polypropylene as the hard section or continuous phase of the alloy material, and through specific molecular structures and processes, a thermoplastic polyolefin alloy with high temperature resistance, thermal aging resistance, weather resistance, high strength, high elongation and flexibility is formed.

Benefits of technology

It realizes the low density, high flexibility, good tensile strength and excellent thermal aging resistance of thermoplastic polyolefin alloys, and has excellent processing behavior, which is suitable for blown film and tensile processing, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842177A_ABST
    Figure CN119842177A_ABST
Patent Text Reader

Abstract

The invention discloses a thermoplastic polyolefin alloy, a preparation method thereof and application of the thermoplastic polyolefin alloy in waterproof coiled materials. The thermoplastic polyolefin alloy comprises PEBB, PP and auxiliary materials; the PEBB has the following molecular structure: # imgabs0 #, wherein x, y, a and b are all polymerization degrees; x + y is equal to 440 to 800; a + b is equal to 1100 to 2500; x / (x + y) is less than 0.05; a / (a + b) = 0.15 to 0.70; the degree of unsaturation of the PEBB is 0.5 to 1.0 percent. The thermoplastic polyolefin alloy material has the characteristics of high temperature resistance, thermal aging resistance, weather resistance, high strength, high elongation, good flexibility, light weight (the density is 0.81) and the like, also has excellent processing behavior, and is easily processed into a waterproof coiled material through film blowing and film stretching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a thermoplastic polyolefin alloy, in particular to a polyethylene-1-butene elastomer modified polyolefin material, and also to a preparation method thereof and application in waterproof coiled materials, belonging to the technical field of novel thermoplastic polyolefin elastic materials (TPO). Background Art

[0002] Polyethylene-1-butene random copolymer has no physical crosslinking nodes in its molecular structure and is not a thermoplastic elastomer. Only when the molecule contains highly crystalline polyethylene segments and randomly distributed polyolefin chain segments can it behave like a thermoplastic elastomer. Existing commercially available polyolefin elastomers (POE) are copolymerized by ethylene and a small amount of 1-butene or 1-octene, and the α-olefin contained in its molecular structure is 10-15%. The presence of 1-butene or 1-octene chain segments in the POE molecule destroys the regularity of the polyethylene chain, but also gives the copolymer excellent transparency and certain elasticity. At room temperature, the crystallization of the polyethylene chain serves as a physical crosslinking point, and the amorphous region of the random copolymer chain as the ethylene 1-butene or 1-octene chain segment comonomer makes the copolymer elastic. The narrow molecular weight distribution makes POE have higher tensile strength and impact resistance, and also shows good processing performance, but its disadvantages are high modulus, high hardness, poor resilience and high crystallinity, and incompatibility with mineral oil. It has been widely used in photovoltaic panels and blending with polyolefin resins, but it is not suitable as a low-hardness elastic material.

[0003] Traditional commercially available carbon-hydrogen rubbers such as ethylene-propylene rubber (EPDM) are copolymerized by ethylene, propylene and dienes. According to their different molecular structure characteristics, there are more than 20 types of applications. The EPDM ethylene-propylene ratio can be changed during the polymerization stage. When the ethylene-propylene ratio changes from 50 / 50 to 80 / 20, the positive effects are: higher green strength, higher tensile strength, higher crystallization, higher glass transition temperature, the ability to convert raw material polymers into granules, and better extrusion properties. The negative effects are poor calendering mixing, poor low-temperature properties, and poor compression set.

[0004] There are 19 types of EPDM currently on the market launched by DOW Chemical, 13 of which are semi-crystalline polymers with a crystallization temperature of 33-46°C. Although the polymer has a large deformation below the crystallization temperature, it still exhibits a high tensile strength. The comprehensive physical properties of this type of polymer decrease with the increase of room temperature. It is not a thermoplastic elastic material. If the vulcanization process is not carried out, the raw rubber has poor heat resistance and is not suitable for direct use. It has commercial value only after vulcanization and molding.

[0005] In "Thermoplastic Elastomers", 99 rubber / plastic blends prepared from 11 rubbers and 9 plastics were reviewed. The study found that to obtain the best performance of the rubber / thermoplastic dynamic vulcanization blend, the surface energy of the two polymers of plastic and rubber must match, the length of the rubber entanglement molecular chain is low, and the crystallinity of the plastic is greater than 15%. When the polarity or surface energy difference between the plastic and the rubber is relatively large, adding a suitable compatibilizer and then dynamically vulcanizing can also obtain a blend with excellent performance. The commercial thermoplastic elastomers (TPV) formed between PP / PE / EPDM and PP / EPDM account for 90% of the total TPV, mainly because PP and EPDM materials have better compatibility, the vulcanization system that can be used for EPDM is relatively mature, and EPDM has very good weather resistance, but the highly oil-filled TPV has poor heat resistance and is not suitable for outdoor coils that can withstand heat to 55-65°C.

[0006] In addition, the existing CA10A and CA10A launched by Lyondebasell belong to thermoplastic polyolefin (TPO), which has high strength, high modulus, high temperature resistance, aging resistance, high elongation and good flexibility, and is mainly used as high temperature resistant roof or color steel tile waterproofing materials, but the existing TPO waterproofing membrane is expensive. The traditional asphalt waterproofing membrane modified by styrene butadiene elastomer has poor aging resistance, high density, poor compatibility between polymer and asphalt, low surface energy between the two, and polymer is easy to precipitate and delaminate from the asphalt phase. The asphalt waterproofing membrane modified by styrene butadiene elastomer is not suitable for leak-proofing of color steel tiles.

[0007] In summary, existing hydrocarbon polyolefin polymers such as TPV, TPO and POE all have defects, and there is no literature report on the preparation of TPO elastomers using polyethylene-polybutylene elastic materials. Summary of the invention

[0008] Aiming at the shortcomings of the existing TPV, TPO, POE and styrene-butadiene elastomer modified asphalt used in waterproof membranes.

[0009] The first object of the present invention is to provide a thermoplastic polyolefin alloy (TPO) with high temperature resistance, heat aging resistance, weather resistance, high strength, high elongation, good flexibility, and light weight (density of 0.81). It also has excellent processing behavior and can be easily processed into waterproof membranes through film blowing and stretching.

[0010] The second object of the present invention is to provide a method for preparing a TPO material, which is simple, low-cost, can be produced using existing mature equipment and processes, and is easy to industrialize.

[0011] The third object of the present invention is to provide an application of a TPO material. The TPO material has excellent processing behavior and can be easily processed into a waterproof membrane by film blowing and stretching. The resulting waterproof membrane exhibits good flexibility, elasticity, tensile strength, excellent heat aging resistance, and low density and lightweight.

[0012] In order to achieve the above technical objectives, the present invention provides a thermoplastic polyolefin alloy (TPO material), which comprises PEBB and PP and auxiliary materials;

[0013] The PEBB has the following molecular structure:

[0014]

[0015] Among them, x, y, a and b are all polymerization degrees; x+y=440-800; a+b=1100-2500; x / (x+y)<0.05; a / (a+b)=0.15-0.70; and the unsaturation degree of the PEBB is 0.5-1.0%.

[0016] The thermoplastic polyolefin alloy of the present invention is a composite material formed by modifying PP using PEBB with a special molecular structure, wherein PEBB is used as the elastic component of the alloy material, and polypropylene is used as the hard segment or continuous phase of the alloy material. The molecular structure of PEBB includes two polybutadiene blocks with different microstructures, wherein the first block is a block mainly composed of the 1,4-polymerization structure of butadiene, i.e., a polyethylene block, wherein the 1,4-polymerization structure accounts for more than 95%, and the block is easy to crystallize, has hard segment properties, can provide polymer physical crosslinking points, can form physical crosslinking with PP, and improve the compatibility of the two, and the second block is a copolymerization block in which the 1,2-polymerization structure and the 1,4-polymerization structure of butadiene are randomly distributed, and has soft segment properties, and the block can form a relatively uniform mixture under the wetting and swelling action of white oil, and the small amount of double bonds remaining therein are micro-crosslinked under high temperature to obtain a dispersed phase, the white oil is contained in the dispersed phase, and the continuous phase and the dispersed phase form a macroscopic structure similar to an island structure without chemical bonds. Based on this, PEBB is an excellent modified material of PP. The thermoplastic polyolefin alloy material prepared by the two has the characteristics of high temperature resistance, heat aging resistance, weather resistance, high strength, high elongation, good flexibility, light weight, etc. It also has excellent processing behavior and is easy to be processed by film blowing and stretching.

[0017] The E segment in the PEBB molecule in the thermoplastic polyolefin alloy of the present invention is a hard segment chain crystallization that can provide a physical crosslinking point for the polymer, giving the polymer high tensile strength and modulus, and the random copolymerization-BB-segment is a soft segment of the polymer, giving the polymer good flexibility and elasticity, and the entire molecule exhibits the behavior of a thermoplastic elastomer. In addition, the trace double bonds in the PEBB molecule provide chemical crosslinking points for the polymer, and the polymer is micro-crosslinked to form a network macromolecule with a certain elastic modulus, thereby increasing the melting temperature and crystallization temperature of the EBB, giving the polymer excellent comprehensive physical properties, and being beneficial to compounding with a polyolefin resin to produce good flexibility, suitable resilience, high elastic modulus, low compression deformation and aging resistance.

[0018] As a preferred solution, the number average molecular weight of the PEBB is 8×10 4 ~16×10 4 , the molecular weight distribution index is M w / M n =1.05~1.15. The PEBB of the present invention has the characteristics of uniform molecular weight distribution and narrow distribution index. The polymers with low and medium molecular weight and narrow molecular fraction have suitable melt index (MFR), are easy to be injection molded, easy to be formed into films, and have good processing performance, giving the product a smooth surface.

[0019] As a preferred solution, in the PEBB molecular structure, a / (a+b)=0.20-0.30.

[0020] As a preferred solution, the crystallinity of the PEBB is 25-40%, and the crystallization temperature T c =50~90℃, melt index MFR 200℃ / 5kg =0.5~7.5g / 10min.

[0021] As a preferred solution, the thermoplastic polyolefin alloy comprises the following components in parts by weight: 100 parts of PEBB, 25-50 parts of PP, 25-33 parts of white oil, 0.15-0.20 parts of antioxidant, and 0.35-0.55 parts of peroxide.

[0022] As a preferred solution, the melt index MFR of the PP is 200℃ / 5kg The preferred polypropylene is commercially available PP (T30). The preferred dosage is PEBB / PP (weight) = 2-4; if the dosage of PP is too high, the elasticity and elongation of the prepared TPO decrease; if the dosage of PP is too low, the crystallization temperature cannot be increased and the heat resistance is poor.

[0023] As a preferred solution, the white oil is at least one of white oil 10#, white oil 32#, white oil 26#, and white oil 150N. The preferred amount of white oil is 25-33% of the mass of PEBB. The PEBB molecules selected in the present invention have a low content of side ethyl groups and are only suitable for a small amount of oil filling. If the oil filling rate is too high, the oil product will seep into the polymer, and the crystallization temperature of the product material will drop, the strength will be low, and the heat resistance will drop; if the oil filling rate is too low, the cost of the prepared product will be too high.

[0024] As a preferred solution, the antioxidant is at least one of antioxidant 1076, antioxidant 3114, and antioxidant 1010. The preferred antioxidant is a commercially available phenolic antioxidant, such as at least one of antioxidant 1076, antioxidant 3114, and antioxidant 1010, and the preferred dosage is 0.15 to 0.20% of the mass of the polyolefin. If the dosage of the antioxidant is too high, the antioxidant will experience frosting migration and contaminate the surface of the product, and if the dosage of the antioxidant is too low, the antioxidant effect cannot be achieved.

[0025] As a preferred solution, the peroxide is di-tert-butyl peroxide diisopropylbenzene (BIPB). The preferred peroxide is a commercially available organic peroxide, such as BIPB, and its preferred dosage is 0.35-0.55% of the mass of PEBB. If the dosage of the peroxide is too high, the crosslinking density of PEBB is large, the prepared TPO alloy material has a low melt index, poor fluidity, and gel or defects appear on the die surface. If the dosage of the peroxide is too low, the micro-crosslinking effect cannot be achieved, and the melting temperature and crystallization temperature of the alloy material are low.

[0026] The present invention also provides a method for preparing a thermoplastic polyolefin alloy, which comprises the steps of uniformly stirring auxiliary materials including peroxide, antioxidant and white oil to form a mother liquor, mixing the mother liquor, PEBB and PP, blending, vulcanizing and extruding the obtained mixture through a twin-screw extruder, and pelletizing to obtain a TPO alloy material.

[0027] As a preferred solution, the temperature of the twin-screw extruder for blending, vulcanization and extrusion is controlled at 200-210°C.

[0028] The invention also provides an application of a thermoplastic polyolefin alloy, which is applied to the preparation of waterproof coiled materials.

[0029] As a preferred solution, the thermoplastic polyolefin alloy is melted and extruded through a single-screw extruder, and then subjected to film drawing, cooling, forming and winding to obtain the waterproof roll material.

[0030] The PEBB of the present invention is obtained by the following preparation method:

[0031] The first step is to heat the anionic polymerization system containing the activator to 85-95°C, then add a certain amount of n-butyl lithium (NBL), and then add a certain amount of butadiene to carry out homopolymerization for 20-25 minutes to form B1-Li + The active polymer B1 is mainly 1,4-addition of butadiene, and also contains a small amount of 1,2-addition units, among which the number of 1,4-addition units is much greater than that of 1,2-addition.

[0032] Step 2: Cool the above polymerization solution, add a certain amount of butadiene and react at 50-65°C for not less than 40 minutes. The resulting polymer exhibits a B1-B2-Li + The active polymer (BR raw rubber) contains a higher proportion of 1,2-addition units in the B2 segment.

[0033] Step 3: Add a certain amount of NBL, co-catalyst and titanocene catalyst into the BR glue solution and react at a certain temperature and hydrogen pressure for not less than 120 minutes to obtain the PEBB glue solution.

[0034] Step 4: Wash and terminate the PEBB glue with a small amount of aqueous solution of tert-decanoic acid, remove volatiles through a twin-screw extruder, extrude, and pelletize to obtain PEBB pellets.

[0035] The anionic polymerization system of the present invention uses cyclohexane as a solvent, and the amount of the solvent is measured based on the mass fraction of the total mass of butadiene in cyclohexane being 10-14%.

[0036] The activator of the present invention is tetrahydrofuran, and the amount of the activator is measured at a concentration of 10 to 20 mg / kg in a cyclohexane solvent. It is worth further explaining that: it is well known that tetrahydrofuran (THF) is a commonly used activator for anionic polymers such as styrene-butadiene polymers (SBS), and THF is greatly affected by polymerization temperature. For example, the higher the polymerization temperature, the lower the 1,2-structure content in the butadiene polymerization chain; the lower the polymerization temperature, the higher the 1,2-structure content. In the present invention, high-temperature polymerization is used in the first stage of polymerization to produce more 1,4-adducts, which is convenient for producing longer polyethylene blocks after hydrogenation. Low-temperature polymerization is used in the second stage to produce more 1,2-adducts, which is convenient for producing more ethyl side chains after hydrogenation, increasing the disordered distribution of hydrogenated polyethylene and poly-1-butene and the elasticity of the entire polymer.

[0037] The polymerization time of the present invention is not less than 20 minutes. The polymerization temperature is a high temperature condition of 85 to 95° C., and the polymerization time is not less than 20 minutes to ensure that the 1,4-addition unit content in the B1 segment is greater than 95%, and the 1,2-addition unit content is less than 5%, or even lower, which is beneficial to the formation of regular block crystallization chain segments of polyethylene after hydrogenation, and improves the tensile strength and crystallization temperature of the PEBB polymer.

[0038] The second stage polymerization time of the present invention is not less than 40 minutes. The temperature of the second stage polymerization is a low temperature condition of 50 to 65°C, and the second stage polymerization time is not less than 40 minutes to ensure that the content of 1,4-addition units in the B2 stage is 30 to 85%, and more preferably 70 to 80%; the content of 1,2-addition units is 15 to 70%, and more preferably 20 to 30%. The preferred 1,4-addition and 1,2-addition units are randomly arranged to ensure that the PEBB polymer has suitable flexibility or elasticity.

[0039] The conditions of the catalytic hydrogenation reaction of the present invention are: n-butyl lithium is used as an activator, a mixed solution of dimethyl phthalate and methyl o-toluate is used as a co-catalyst, dicyclopentadiene titanium dichloride is used as a main catalyst, the hydrogen pressure is 13-16 bar, the temperature is 75-110° C., and the hydrogenation time is not less than 120 minutes.

[0040] The dosage of the main catalyst of the present invention is 0.04-0.06g / 100g polymer; the dosage of the co-catalyst is 1 / 5-1 / 8 times the molar amount of the main catalyst; the dosage of the activator is 6-10 times the molar amount of the co-catalyst. Under the preferred catalytic hydrogenation conditions, the hydrogenation degree of the polymer can be guaranteed to be 99.0-99.50%.

[0041] The preparation method of the TPO alloy material of the present invention is as follows: BIPB and antioxidant powder are added to white oil and stirred at 30-50°C until the powder is completely dissolved to form a mother liquid, and then the mother liquid, EBB and PP are placed in a mixer and mixed at a speed of 1500RPM for not less than 60 seconds, and the mixture is discharged. The mixture is then placed in a twin-screw extruder at 200-210°C for blending, vulcanization, extrusion and pelletizing to obtain the TPO alloy material.

[0042] The method for preparing waterproof coiled material from TPO alloy material of the present invention is as follows: placing TPO alloy material in a single screw extruder at 200-210°C for melting, extrusion, film drawing, cold air blowing cooling molding, winding, and packaging to obtain waterproof coiled material. The preferred thickness of TPO alloy waterproof coiled material can be 1mm, 1.5mm and 2mm, and the width can be selected to be 1m, 2m, and 3m. The joint connection of this TPO alloy waterproof coiled material during laying construction can be selected by hot melt bonding.

[0043] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0044] Aiming at the shortcomings of the existing TPV, TPO, POE and styrene-butadiene elastomer modified asphalt used in waterproof membranes.

[0045] The TPO alloy of the present invention uses polyethylene-1-butene block copolymer as the main component of the elastic material, and the polypropylene in the component is used as the hard segment or continuous phase of the alloy material. The selected EBB forms a relatively uniform mixture under the wetting of white oil, and is micro-crosslinked under high temperature to obtain a dispersed phase. The white oil is contained in the dispersed phase, and the continuous phase and the dispersed phase form a macroscopic structure similar to a sea-island structure without chemical bonds.

[0046] The TPO alloy and waterproof coiled material of the present invention exhibit good flexibility, elasticity, tensile strength, excellent heat aging resistance and low density and light weight, and also exhibit excellent processing behavior and are easy to blow and stretch.

[0047] The TPO alloy and waterproof coiled material of the present invention can be prepared by using existing mature technology, and the method is simple, easy to control and industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is the GPC spectrum of polymer B1-B2-1# raw rubber in PEBB preparation example 1.

[0049] Figure 2 PEBB Preparation Example 1 Hydrogenated Polymer PEBB-1#H 1 -NMR.

[0050] Figure 3 H of thermoplastic polyolefin CA10A (TPO) produced by Lyondebasell 1 -NMR.

[0051] Figure 4 DSC analysis of TPO prepared in PEBB Preparation Example 1. DETAILED DESCRIPTION

[0052] The following examples are intended to further illustrate the present invention in detail and are not intended to limit the scope of protection of the claims of the present invention.

[0053] In the following examples, the number average molecular weight and molecular weight distribution index of the polymers were determined by gel permeation chromatography (GPC); 1 -NMR spectroscopy was used to quantitatively determine the microstructure of the polymer; the crystallinity, melting temperature and crystallization temperature of the TPO alloy were determined using a differential scanning calorimeter (DSC); the mechanical properties of the TPO alloy were tested according to the GB / T36089-2018 method.

[0054] Example 1

[0055] In a 5-liter polymerization kettle under nitrogen protection, 3500 mL of cyclohexane and 0.04 mL of tetrahydrofuran (THF) were added in sequence, and the temperature was raised to 85°C with hot water, and then 5.2 mL of 0.5 mol / L NBL and 110 mL of the first butadiene were added, and the polymerization was carried out for 25 minutes under a nitrogen pressure of 4.0 bar; then the temperature of the polymerization kettle was lowered to 52°C, and 250 mL of the second butadiene was added, and the polymerization was carried out for 40 minutes at a temperature not exceeding 65°C. The original rubber was obtained, and the GPC spectrum of the original rubber is shown in Figure 1 .

[0056] 3.8 mL of 0.5 mol / L NBL, 4 mL of 0.02 mol / L cyclohexane solution of dimethyl phthalate and methyl o-toluate (molar ratio 1:1), and 0.18 g of dicyclopentadiene titanium dichloride were added to the original glue solution, and the mixture was stirred and hydrogenated for 120 min at a hydrogen pressure of 14 bar and a temperature of 100°C to obtain EBB glue solution. The hydrogenated glue solution was then stirred and terminated with 30 mL of 10% tert-decanoic acid and 80 mL of water. After centrifugal dehydration, the glue solution was dry-extracted in a twin-screw extruder to remove the solvent and a small amount of water, and underwater pelletization was performed to obtain EBB transparent pellets (labeled as PEBB-1, nuclear magnetic hydrogen spectrum shown in Figure 2 , the characteristic behaviors of the polymers are shown in Table 1.

[0057] Example 2

[0058] The relevant process conditions in Example 1 were kept unchanged, except that the amount of NBL used in the polymerization reaction was changed to 4.4 mL, and the amount of butadiene used in the first and second reactions was 130 mL and 260 mL, respectively.

[0059] Results The prepared polymer was designated as PEBB-2, and its behavior parameters are shown in Table 1.

[0060] Example 3

[0061] The relevant process conditions in Example 1 were kept unchanged, except that the amount of NBL used in the polymerization reaction was changed to 3.4 mL, the amount of THF used was changed to 0.07 mL, and the amount of butadiene used in the first and second reactions was 150 mL and 290 mL, respectively.

[0062] Results The prepared polymer was designated as PEBB-3, and its behavior parameters are shown in Table 1.

[0063] Example 4

[0064] The relevant process conditions in Example 1 were kept unchanged, except that the amount of NBL used in the polymerization reaction was changed to 3.8 mL, and the amount of butadiene used in the first and second reactions was 180 mL and 250 mL, respectively.

[0065] Results The prepared polymer was designated as PEBB-4, and its behavior parameters are shown in Table 1.

[0066] Example 5

[0067] As a control.

[0068] The relevant process conditions in Example 3 were kept unchanged, except that the amount of NBL used in the polymerization reaction was changed to 3.2 mL, the amount of THF used was changed to 0.07 mL, and the amount of butadiene used in the first and second reactions was 160 mL and 300 mL, respectively.

[0069] Results The prepared polymer was designated as PEBB-5, and its behavior parameters are shown in Table 1.

[0070] Table 1 Characteristic analysis of original rubber and hydrogenated rubber PEBB in the examples

[0071]

[0072]

[0073] Melt index: tested at 200℃ / 5kg.

[0074] Example 6

[0075] PEBB-1, PEBB-2, PEBB-3, PEBB-4 and PEBB-5 and commercially available ethylene propylene diene rubber DOW4570 (called hydrocarbon rubber) are respectively labeled as Example 1#, Example 2#, Example 3#, Example 4#, Example 5# and control sample DOW4570. These six rubber samples are respectively blended and granulated with other components in the TPO alloy formula of the present invention according to the preparation method of the present invention. The corresponding formulas are shown in Table 2.

[0076] Table 2 TPO alloy formula

[0077] Hydrocarbon rubber PP T30 150N white oil BIPB Antioxidant 3114 Example 1# 100 50 25 0.55 0.16 Example 2# 100 40 28 0.50 0.17 Example 3# 100 30 30 0.42 0.18 Example 4# 100 25 33 0.35 0.20 Example 5# 100 60 35 0.65 0.17 Control sample DOW4570 100 35 28 0.45 0.25

[0078] The TPO alloy prepared in Table 2 and the CA10A pellets produced by Lyondebasell were hot-melt pressed at 175°C, and the physical properties of the pressed rubber are shown in Table 3.

[0079] Table 3 Physical and mechanical properties of pressed TPO alloy rubber

[0080]

[0081] Note: MFR is melt index, g / 10min, 230℃ / 2.16Kg.

Claims

1. A thermoplastic polyolefin alloy, characterized in that: Contains PEBB and PP and auxiliary materials; The PEBB has the following molecular structure: in, x, y, a and b are the degrees of polymerization; x+y=440~800; a+b=1100~2500; x / (x+y)<0.05; a / (a+b)=0.15-0.70; The unsaturation degree of the PEBB is 0.5-1.0%.

2. A thermoplastic polyolefin alloy according to claim 1, characterized in that: The number average molecular weight of the PEBB is 8×10 4 ~16×10 4 , the molecular weight distribution index is M w / M n =1.05~1.

15.

3. A thermoplastic polyolefin alloy according to claim 1 or 2, characterized in that: The crystallinity of the PEBB is 25-40%, and the crystallization temperature T c =50~90℃, melt index MFR 200 ℃ / 5kg =0.5~7.5g / 10min.

4. A thermoplastic polyolefin alloy according to claim 1 or 2, characterized in that: The invention comprises the following components in parts by weight: 100 parts of PEBB, 25 to 50 parts of PP, 25 to 33 parts of white oil, 0.15 to 0.20 parts of antioxidant and 0.35 to 0.55 parts of peroxide.

5. A thermoplastic polyolefin alloy according to claim 4, characterized in that: The melt index MFR of the PP 200 ℃ / 5kg 3~15g / 10min.

6. A thermoplastic polyolefin alloy according to claim 4, characterized in that: The white oil is at least one of white oil 10#, white oil 32#, white oil 26#, and white oil 150N.

7. A thermoplastic polyolefin alloy according to claim 4, characterized in that: The antioxidant is at least one of antioxidant 1076, antioxidant 3114, and antioxidant 1010.

8. A thermoplastic polyolefin alloy according to claim 4, characterized in that: The peroxide is di-tert-butyl diisopropylbenzene peroxide.

9. The method for preparing a thermoplastic polyolefin alloy according to any one of claims 1 to 8, characterized in that: The auxiliary materials including peroxide, antioxidant and white oil are stirred evenly to form a mother liquor, the mother liquor, PEBB and PP are mixed, the obtained mixture is blended, vulcanized and extruded through a twin-screw extruder, and pelletized to obtain a thermoplastic polyolefin alloy.

10. The method for preparing a thermoplastic polyolefin alloy according to claim 9, characterized in that: The temperature of the twin-screw extruder for blending, vulcanization and extrusion is controlled at 200-210°C.

11. The use of a thermoplastic polyolefin alloy according to any one of claims 1 to 8, characterized in that: Used in the preparation of waterproof membrane.

12. The use of a thermoplastic polyolefin alloy according to claim 11, characterized in that: The thermoplastic polyolefin alloy is melted and extruded through a single-screw extruder, and then subjected to film drawing, cooling, forming and winding to obtain a waterproof roll material.